Teachers and Student Difficulties in Teaching ESP for Tourist Department - Yulianti Koban, Katarina; Antonia Lema, Maria (Udayana Journal of Social Sciences and Humanities, 2020)
This study aimed at investigating the difficulties of teaching ESP For Tourism Department. The data where taken from through observation, interview and study documents. Data collected by observation, interview and documentation, tthen, the researcher will write down the results of interviews with the English teacher and students This research shows that Professional English teachers often find it difficult when they have to teach English for Specific Purpose (ESP) as they need to do extra works like doing need analysis and creating the specific syllabus before teaching to make sure that the teaching-learning process will go smoothly. Student teachers, who have less experience in teaching, are likely to face greater difficulties in teaching ESP.